The “angiogenesis-plaque stability paradox” in atherosclerosis pathogenesis - Yan, Fei; Sun, Si-yang; Wu, Hong (Frontiers in Cardiovascular Medicine, 2025)
Intraplaque angiogenesis, a critical mechanism in the pathological progression of atherosclerosis (AS), exhibits a paradoxical role by providing nutrients and repair support for plaques while simultaneously contributing to plaque instability and rupture. Current research on intraplaque angiogenesis primarily focuses on molecular mechanisms, cellular interactions, and metabolic regulation; however, its dual effects on plaque stability remain underexplored. This review elucidates the mechanisms underlying the angiogenesis-plaque stability paradox, including the glycolysis-lactate-lactylation modification axis, mast cell-mediated inflammatory responses, and angiogenic maturation and stabilization mechanisms, and discusses their roles and associated regulatory pathways in AS pathogenesis. These insights aim to potentiate atherosclerotic plaque stabilization and refine predictive accuracy for acute cardiovascular events.